A Study of the use of Physical Evidence as a way of Generating Perception of Service Quality: a case study of Brazilian hospitals - Loures, Carlos Augusto da Silva; Campomar, Marcos Cortez (Review of Business Management, 2007)
The aim of this paper is to study the use of physical evidence as a way to generate service quality perceptions from clients of hospitals. The realization of an exploratory research is directly related to the low academic production on the subject in Brazil. In the first part of the paper we present a literature review including: the importance of services; health care services; service quality; and physical evidence. In the second part of the paper are presented the methodology and the results of a field research made with the use of the case study method in order to verify how the concept of physical evidence is practiced by Brazilian hospitals. In the third part we conclude that in general the actions developed by the researched organizations are coherent with the practices described in the international literature. Also in the third part we present the limitations of the study and offer suggestions for future researches on the subject. Key-words: Physical evidence. Service quality. Hospitals.